Dynamics of Concentration in Gross Domestic Product achieved in Romania's Agriculture - Agatha POPESCU; Valentin SERBAN (Communications of International Proceedings, 2021)
The paper analyzed the concentration degree in Gross Domestic Product obtained in agriculture in the territory of Romania. For this purpose, the data provided by National Institute of Statistics  available for the period 2009-2018 were taken into consideration and four concentration indices: Herfindahl-Hirschman Index, Normalized Herfindahl-Hirschman Index, Gini-Struck Index and Concentration Coefficient were calculated. The obtained results proved low values of the concentration indices reflecting a relative uniformity among the eight microregions of Romania in producing GDP from the agricultural sector. However, a slight increasing trend of the values of concentration indices was noticed in four regions of development: South Muntenia, South East region, West region and South West Oltenia, in other three micro regions: North West, Center, and North East was noticed a slight decreasing trend, while Bucharest-Ilfov microregion is atypical for agriculture being small and including the capital. However, a few deviations appeared across the years during the analized interval, but being unsignificant. Knowing the actual state of GDP produced in agriculture at the national and regional level is a useful tool for setting up the future development strategy  which has to be adapted to the local needs. It is also a basis in alloting the EU funds for increasing productivity, efficiency and competitiveness in agriculture and rural areas.
Keywords: Agriculture; Gross Domestic Product; Concentration; Romania.